THE INFLUENCE OF LEADERSHIP AND WORK MOTIVATION ON THE PERFORMANCE OF STATE CIVIL APPARATUS THROUGH JOB SATISFACTION (STUDY AT THE EAST BARITO REGENCY DPRD SECRETARIAT) - Ucok Tigora Limbong; Sutrisno, Sutrisno (Jurnal Ekonomi, 2023)
This research aims to determine and analyze: the significant influence of leadership on job satisfaction; Significant influence of work motivation on job satisfaction; Significant influence of leadership on performance; Significant influence of work motivation on performance; The significant influence of Job Satisfaction on Performance; The influence of leadership on performance through job satisfaction, and the influence of work motivation on performance, State Civil Apparatus (ASN) at the DPRD Secretariat of East Barito Regency. The data collection technique in this research was by distributing questionnaires to a sample of 31 State Civil Servants within the DPRD Secretariat of East Barito Regency. The data analysis technique used was Smart PLS Version 3.2.0. The research results state that leadership has a significant effect on job satisfaction; Work motivation has a significant effect on Job Satisfaction, Leadership has a significant effect on Performance, Work motivation has a significant effect on Performance, Job Satisfaction has a significant effect on Performance, Job satisfaction mediates the effect of leadership on Performance and, Job satisfaction mediates the effect of work motivation on Performance, State Civil Apparatus (ASN) at the East Barito Regency DPRD Secretariat